Religion in the middle east - "Arberry, A.J.( ed.)" (Cambridge, 1969)
It is generally accepted that the Middle East witnessed the ancient rise of monotheism and its dissemination. The three faiths predominantly concerned - Judaism, Christianity, and Islam - have retained their separateness and have been in different degrees torn asunder by schisms; but less well known has been the degree of co-operation between the three faiths and their multifarious sects, throughout history. First published in 1969, Religion in the Middle East aims to give a factual account of these three religions and their sects, in concord and conflict, from an historical perspective. The focus was on the significance of Islam, considered to be the dominant religion of the Middle East since the seventh century. Experts from many parts of the world contributed individual chapters, and the whole work was co-ordinated by a team of leading scholars, making it an erudite study that will be of interest to anyone interested in the historical impact of Islam in the Middle East.
Keywords: Religion